Assessment Attributes on Effective Construction Management for Property Developers in Malaysia - Ayob Norizam; M.A Malek; I Mohamad (ASEAN Journal on Science and Technology for Development, 2014)
Property developers are financially capable of running construction projects. Nevertheless, in Malaysia it was found that many of these construction practitioners failed to provide effective construction management which affected society. The success of a project and its Critical Success Factors (CSFs) are considered as tools to improve the effectiveness of project management. Eventhough many researchers have conducted studies on CSFs, the use of CSFs has remained ambiguous. The main objective of this study is to validate the proposed assessment attributes obtained from the property developers based on CSFs. A questionnaire survey was conducted to validate this predeterminedattributes. Comparison was made with attributes from Project Management Book of Knowledge in order to explore the underlying suitability of the proposed attributes with the study area in terms of climate, economy, etc. Factor Analysis was adopted to investigate the group component relationships. This study focuses on the link between CSFs and the implementation of an effective construction management specifically for property developers in Malaysia.